Proses Pembuktian Tindak Pidana Pada Anak Korban Pencabulan Di Kota Gorontalo (Studi Kasus Pengadilan Negeri Gorontalo) - firman mahmud; Kindom Makkulawuzar; Syarif Lamanasa (Fakultas Hukum Universitas Ichsan Gorontalo, 2026)
This study aims to find out how the process of proving the crime of child molestation is and to find out what factors inhibit the process of proving the crime of child molestation. This study uses the Normative-Empirical Legal Research method (applied law research), which is a study that uses normative-empirical legal case studies in the form of legal behavior products. The results of the study show that the process of proving the crime of child molestation is carried out from several stages in the trial, the first is the statement of the victim's child who in the trial results explained that the defendant's actions were not true but the victim's child's statement was ordered by Mr. Ulfa. Second, the witness's statement in the trial contradicts the victim's child's statement, third, the results of the post-mortem issued by social workers/social rehabilitation assistance in the trial, the questions asked to the victim's child were all answered only by Mr. Ulfa and the questions given to the victim's child were only questions in the police BAP, not specific questions. And the obstacles in the process of proving the crime of sexual abuse are first, the victim is afraid to tell the truth about the incident because he was threatened by someone else, second, the witness gives false information so that the examination of the victim's child is carried out a second time which makes the decision on a case take so long, finally, the law enforcement party has limited understanding and expertise of law enforcement in handling cases of sexual abuse.